Hydrogen Storage Materials
A perovskite-type oxide hydrogen storage material with reduced barium occupancy and metal catalyst interaction allows for lower temperature hydrogen release, addressing the challenge of temperature-dependent hydrogen release in existing materials.
Patent Information
- Application Number
- JP2021040237
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-12
- Publication Date
- 2024-12-23
- Estimated Expiration
- 2041-03-12
AI Technical Summary
Existing hydrogen storage materials with perovskite oxide structures face challenges in releasing hydrogen at low temperatures, and there is a lack of effective methods for storing and releasing hydrogen using dilute hydrogen gas, particularly in environments where spontaneous regeneration is required.
A hydrogen storage material with a perovskite-type oxide structure is developed, comprising barium (Ba), zirconium (Zr), and optionally indium (In) or yttrium (Y), where the A site occupancy of barium is reduced below 1.0, destabilizing the oxygen coordination and allowing hydrogen to be introduced under milder conditions, facilitating lower temperature release through a process involving a metal catalyst.
The material achieves hydrogen release at lower temperatures by destabilizing oxygen coordination, enabling efficient storage and release of hydrogen, suitable for applications such as hydrogen storage, fuel cell anodes, and catalyst carriers.
Smart Images

Figure 0007603930000009 
Figure 0007603930000010 
Figure 0007603930000011
Abstract
Description
[Technical field]
[0001] The present invention relates to a hydrogen storage material, and more particularly to a hydrogen storage material containing barium and zirconium and having a perovskite-type oxide structure. [Background technology]
[0002] There are known ceramic materials that absorb and release hydrogen, such as metal hydrogen storage materials. For example, perovskite-type oxides represented by ABO3, which have hydrogen absorption and release capabilities, are known as hydrogen storage materials.
[0003] This perovskite oxide consists of cations (A site ions, B site ions) that occupy the A and B sites, and oxygen ions (O 2- ) and the cations occupying the A site have a relatively large ionic radius, while the cations occupying the B site have a relatively small ionic radius.
[0004] Compounds with a perovskite oxide structure are known to have a variety of combinations of cations at the A and B sites, and can form a structure that generates oxygen vacancies, holes, and electrons to the extent that the overall charge balance is maintained, thereby achieving electrical neutrality.
[0005] Among these, composite oxides in which alkaline earth metals such as Ba, Sr, and Ca are placed on the A site and tetravalent cations such as Zr and Ti are placed on the B site are known to function as proton conductors.
[0006] In particular, barium zirconate (BaZrO3) is frequently used as an electrolyte material for medium- to high-temperature fuel cells.
[0007] In addition, barium zirconate, which is used as a proton conductor, can be doped with metal M (trivalent impurity cations such as Y, Er, Sc, In, Ce, Gd, and Al) to occupy some of the tetravalent cation sites on the B site, resulting in an AB 1-y My O 3-δ It is possible to form oxygen vacancies corresponding to δ in the above formula.
[0008] It is known that when water vapor in the gas phase is absorbed into the oxygen vacancies, two hydroxyl groups are formed that undergo hydrogen bonding with the surrounding lattice oxygen, resulting in proton conductivity.
[0009] Ba with cation M being Y 1.0 Zr 1-y YyO 3-δ It is experimentally known that this material system has the best ionic conductivity when used at temperatures between 400°C and 600°C, and its fundamental effects based on first-principles calculations have been verified.
[0010] Hydrogen storage materials made of such perovskite oxides are inherently oxides, and therefore have excellent high-temperature resistance, resistance to steam oxidation, and high-temperature oxidation properties, and are expected to be usable in environments where it is difficult to use metal-based hydrogen storage materials.
[0011] In other words, it is a material that can store and release hydrogen by controlling differences in temperature and pressure, and is a hydrogen storage material that is expected to be used in the aforementioned hydrogen storage applications, steam reforming, fuel cell anode catalysts, and as a catalyst or catalyst support that controls the temporary storage and release of hydrogen in dehydrogenation reactions and nitrogen oxide purification reactions in exhaust gases.
[0012] On the other hand, barium titanate (BaTiO3), which also has Ba on the A site and Ti on the B site, is originally known as a dielectric material for ceramic capacitors.
[0013] Regarding the hydrogen release performance of barium titanate, Patent Document 1 discloses a titanium-containing perovskite oxide that releases hydrogen at temperatures of 450° C. or lower.
[0014] However, the introduction of hydrogen into barium titanate as a hydrogen releaser requires a heat treatment in the presence of a metal hydride reagent, CaH2, which is a strong reducing agent, and requires a process to remove calcium oxide, which remains as a residue after the heat treatment, from the synthesized compound using an ammonia solution or the like.
[0015] Therefore, in the hydrogen storage material, when hydrogen is released from the material, there is a problem with spontaneous regeneration in the usage environment. Furthermore, the patent document does not describe the problems associated with the storage method using hydrogen gas, particularly dilute hydrogen gas, and the release of hydrogen. Furthermore, from the perspective of storing hydrogen in perovskite hydrogen storage materials, as well as lowering the temperature range at which they can be used as catalysts and catalyst supports, and expanding the temperature range in which they can be used, there is a demand for them to have the ability to release hydrogen at lower temperatures. [Prior art documents] [Patent documents]
[0016] [Patent Document 1] International Publication No. 2013 / 008705 Summary of the Invention [Problem to be solved by the invention]
[0017] An object of the present invention is to provide a hydrogen storage material having a perovskite-type oxide structure with a lower hydrogen release temperature. [Means for solving the problem]
[0018] As a result of intensive research into achieving the above-mentioned object, the present inventors have discovered that it is possible to synthesize a hydrogen storage material capable of absorbing and releasing hydrogen at low temperatures by using hydrogen gas as a raw material for hydrogen absorption (initial activation) in a perovskite-type oxide having barium ions at the A site and zirconium at the B site, and by bringing the raw material oxide into contact with a metal catalyst excellent in hydrogen dissociation and deoxidation ability and performing hydrogen absorption (initial activation) under milder conditions, thereby completing the present invention.
[0019] That is, the hydrogen storage material of the present invention has a perovskite-type oxide structure whose basic structure is represented by ABO3, The A site is barium (Ba) and the B site is zirconium (Zr), and a part of the A site and / or the B site is substituted with a metal (M), and within the perovskite-type oxide structure Contains hydrogen (H). The elemental composition is in the range of 12 to 21 atomic % of barium (Ba), 8 to 21 atomic % of zirconium (Zr), 50 to 62 atomic % of oxygen (O), 4 to 16 atomic % of metal (M), and 2 to 13 atomic % of hydrogen (H). the law of nature, The composition has a perovskite first phase and a perovskite second phase obtained by Rietveld analysis of an X-ray diffraction spectrum, and the content of the perovskite first phase is at least 60 mol% or more; The metal (M) is indium (In) or yttrium (Y). Effect of the Invention
[0020] According to the present invention, in a perovskite oxide in which the A-site ion is a barium ion and the B-site ion is a zirconium ion, hydrogen is introduced into the perovskite oxide in a state in which the oxygen coordination in the structure is destabilized, thereby allowing the perovskite oxide to contain a desired amount of hydrogen, thereby providing a hydrogen storage material that releases hydrogen at a lower temperature. [Brief description of the drawings]
[0021] [Figure 1] 1 is a graph showing the change in d-DTAH2-N2 value and the change in hydrogen concentration in the hydrogen absorption and activation process of Comparative Example 3. [Diagram 2] 1 is a graph showing the change in d-DTAH2-N2 value and the change in hydrogen concentration in the hydrogen absorption and activation process of Comparative Example 4. [Diagram 3] 1 is a graph showing changes in DTA value during the hydrogen absorption and activation process in Comparative Examples 3 and 4. [Figure 4] 13 is a graph showing hydrogen detection current values during a temperature rise process in a hydrogen absorption and activation step in Comparative Example 3 and Comparative Example 4. [Diagram 5] 1 is a graph showing the change in d-DTA value during the hydrogen absorption and activation process in Examples 4 and 5. [Figure 6] 1 is a graph showing hydrogen release behavior in Examples 4 and 5. [Figure 7] FIG. 1 is a graph showing the relationship between the amount of released hydrogen and the Ba content. [Figure 8] FIG. 1 is an XRD spectrum diagram of Comparative Example 4 and Example 5. [Figure 9] 1 is a graph showing the results of SIMS measurement of Examples 4 and 5 and Comparative Examples 3 and 4. [Figure 10] FIG. 2 is a diagram showing the relationship between the composition of a raw material oxide and oxygen vacancies. [Figure 11] FIG. 1 is a schematic diagram of an apparatus for measuring the electrical behavior and released gas characteristics of raw oxide during the activation process. [Figure 12] FIG. 1 is a graph showing the relationship between the temperature during activation treatment of a raw oxide with a metal catalyst and the oxygen / hydrogen detection current. [Figure 13] 1 is a comparison of Rwp values in Rietveld analysis of Comparative Example 4. [Figure 14] FIG. 1 is an XRD spectrum diagram showing that In2O3 is produced depending on the Ba content. [Figure 15] 1 is a graph showing the relationship of the banding energy of In2O3. [Figure 16] FIG. 4 is a diagram showing the relationship between the treatment temperature during hydrogen absorption and the hydrogen atom concentration in a hydrogen absorption material. [Figure 17] FIG. 13 is a diagram illustrating the relationship between the hydrogen storage material of Comparative Example 6 and gas flow when hydrogen permeation is confirmed. [Figure 18] 1 is a graph showing the difference in effect of the metal catalyst between Comparative Example 6 and Example 9. [Figure 19] FIG. 1 is a schematic diagram showing the hydrogen storage material of the present invention when used as a carrier catalyst. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] The hydrogen storage material of the present invention will now be described in detail. The hydrogen storage material has a perovskite-type oxide structure whose basic structure is represented by the general formula ABO3, and contains barium (Ba), zirconium (Zr), and oxygen (O), and further contains a metal (M) and hydrogen (H). The elemental composition is 12-21 atomic % barium (Ba), 8-21 atomic % zirconium (Zr), 50-62 atomic % oxygen (O), 4-16 atomic % metal (M), Hydrogen (H) is within the range of 2 to 13 atomic %, and the metal (M) is indium (In) or yttrium (Y).
[0023] The composition of the hydrogen storage material is such that the site occupancy rate of barium ions at the A site is less than 1.0, and the more the occupancy rate is reduced below 1.0, the more the amount of hydrogen absorbed and released increases.
[0024] When the site occupancy rate of the barium ion in the A site is reduced below 1.0, for example, the existence of a structure in which In is located in the A site becomes effective. The presence of a metal (M) in the A site locally distorts the lattice, which makes the oxygen in the perovskite oxide structure energetically unstable, lowering the hydrogen release temperature.
[0025] On the other hand, in the process of introducing hydrogen into a raw oxide (hereinafter, simply referred to as "raw oxide") containing barium (Ba), zirconium (Zr), oxygen (O), and a metal (M) before hydrogen absorption, the reaction, particularly in the low temperature range, involves a process in which deoxidation from the raw oxide proceeds first, and then hydrogen is introduced into the deoxidization site as a hydroxyl group, and therefore the start temperature of hydrogen release, which is the reverse reaction of the introduction reaction, is also lowered.
[0026] <Preparation of hydrogen storage materials: Preparation of raw oxides> The hydrogen storage material can be produced by subjecting a raw material oxide to an activation treatment for absorbing hydrogen.
[0027] The raw material oxides may be prepared by known methods for producing composite oxides, such as calcination / sintering or physical vapor deposition, and the following methods can be used.
[0028] For example, oxides, hydroxides, nitrates, and metal complexes of barium carbonate, zirconium, yttrium, and indium are weighed out to a predetermined ratio, mixed, ground, and dried in a dry system or in a wet system in which grinding and mixing is performed using a bead mill, and then fired in an air atmosphere at 1000°C to 1500°C for 1 to 12 hours to obtain the powder.
[0029] In addition to the above-mentioned methods using firing and sintering, physical vapor deposition methods such as sputtering, PLD (pulsed laser deposition), and atmospheric plasma, which are known as common methods for forming oxide thin films, can also be used to produce raw oxides.
[0030] <Preparation of hydrogen storage materials: Conditions for the initial activation process of raw oxides> A desired amount of hydrogen can be absorbed in the raw oxide by heating the raw oxide to 150° C. to 800° C. in a hydrogen atmosphere with a hydrogen concentration of 5 vol % or more while in contact with a metal catalyst.
[0031] By absorbing hydrogen into the raw oxide, a new phase is generated, making it possible to form a hydrogen storage material. As for the formation of the new phase, at 150°C to 400°C, a second perovskite phase that contributes to lowering the temperature of hydrogen release is formed, and at 400°C to 800°C or higher, a first perovskite phase that contributes to lowering the temperature of hydrogen release and is responsible for transport and structural stability is formed.
[0032] <Types of metal catalysts> Examples of the metal catalyst include palladium (Pd), platinum (Pt), nickel (Ni), and cobalt (Co).
[0033] <Method of contact with metal catalyst> Among the methods for contacting the raw oxide with a metal catalyst, known methods for directly contacting the raw oxide with a metal catalyst can be used, such as coating of a metal paste, electroless plating, vapor deposition, impregnation, support, etc. It is also possible to mix the raw oxide with the metal catalyst as an impurity oxide phase, or to separate and precipitate a metal phase in a process as in the above-mentioned example of In, and have it function as a catalyst in the process.
[0034] As another embodiment, it is possible to use a hydrogen-permeable metal having catalytic action, as described below. By depositing or forming a raw oxide on the hydrogen-permeable metal foil having catalytic action by sputtering, PLD, atmospheric plasma, sol-gel method, or paste, the raw oxide can be endowed with the function of absorbing and releasing hydrogen.
[0035] On the other hand, rather than placing the metal catalyst directly on the raw oxide, it is also possible to obtain the same effect by coating the equipment used in the activation process with the metal catalyst, such as a Pt plate, to ensure contact during the treatment. Therefore, the raw oxide can also be brought into contact with the metal catalyst and absorbed hydrogen by stirring the raw oxide using the inner surface of a container or a stirrer having a metal catalyst on its surface. EXAMPLES
[0036] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the following examples.
[0037] <Raw material oxide and catalyst contact method in Example 1 and Comparative Example 1> Barium carbonate (BaCO3), zirconium oxide (ZrO2), and yttrium oxide (Y2O3) powders were weighed out to achieve the specified metal composition ratio, wet-mixed, and then uniaxially molded at 10 MPa. The mixture was then molded into a tablet shape at 100 MPa to a diameter of 12 mm and a thickness of 2 mm.
[0038] The obtained CIP molded body was sintered in an air sintering furnace at 1500° C. for 12 hours to obtain pellets of Comparative Example 1. Furthermore, palladium (Pd) was deposited to a thickness of 50 nm on one surface of the obtained sintered pellet, thereby preparing a pellet with a metal catalyst before activation treatment in Example 1.
[0039] <Method of contacting raw material oxides and catalysts in Examples 2 to 8 and Comparative Examples 2 to 5> Powders of barium carbonate (BaCO3), zirconium oxide (ZrO2), and indium oxide (In2O3) were weighed out to obtain the specified metal composition ratio, and then wet-mixed. The sintering aid zinc nitrate Zn(NO3)2 was added in a ratio of Zn:Ba = 0.035:1, and wet-mixed.
[0040] Thereafter, uniaxial molding at 10 MPa was performed, and the CIP molded body obtained by molding at 100 MPa using a tablet molding machine was sintered in an atmospheric sintering furnace at 1500°C for 12 hours to obtain pellets of Comparative Example 2. Moreover, pellets of Comparative Example 3 and Comparative Example 4 were obtained in the same manner as Comparative Example 2 except for changing the metal composition ratio.
[0041] Palladium (Pd) was deposited to a thickness of 50 nm on one surface of the pellet of Comparative Example 2 to obtain a pellet with a metal catalyst before activation treatment of Example 2.
[0042] In addition, a commercially available Pt paste was applied to the pellets of Comparative Example 2, Comparative Example 3, and Comparative Example 4, dried, and then fired at 800°C to obtain pellets with metal catalyst before activation treatment of Example 3, Example 4, and Example 5, respectively.
[0043] Examples 6, 7, and 8 were also produced in the same manner as Comparative Example 2, except for changing the metal composition ratio. After producing a sintered pellet, a commercially available Pt paste was applied and dried, followed by firing at 800°C. A hydrogenation treatment was then performed under the conditions described below. The Pt paste was then removed with sandpaper to obtain a black pellet, which was then crushed in a mortar.
[0044] The black powder obtained in Example 6 was heated in an N2 atmosphere at an elevated temperature of 900°C while confirming the release of hydrogen to obtain a whitened sample, which was used as Comparative Example 5.
[0045] <Method of contacting raw material oxide with catalyst in Comparative Example 6 and Examples 9 and 10> All of the raw oxides in Comparative Example 6 and Examples 7 and 8 were obtained by forming a 1.0 μm oxide thin film on a commercially available 50 μm pure palladium foil by magnetron sputtering.
[0046] A commercially available 50 μm pure palladium foil was placed in the chamber of a magnetron sputtering device, and a Pd foil with a thickness of 50 μm and dimensions of 100 mm square was placed. -6 After that, Ar gas was introduced into the chamber to make the pressure in the chamber 3.0×10 -1 While keeping the pressure in the Pd foil at 1 Pa, film formation was carried out under conditions of 800 V and 5 kW for 8 to 10 hours, and a raw oxide having a thickness of 1.0 μm was formed on the Pd foil, thereby obtaining samples of Comparative Example 6, Example 9, and Example 10.
[0047] The oxide target used had a metal molar composition ratio of Ba:Zr:In=37:32:32, and raw oxide films of Comparative Example 6 and Example 9 were obtained. Similarly, a raw oxide film of Example 10 was obtained by deposition using a target having a metal molar composition ratio of Ba:Zr:Y=39:41:20.
[0048] The oxide film after deposition is amorphous, but becomes crystalline when heat-treated at 400°C to 700°C.
[0049] <Initial activation: Hydrogen absorption> The raw material oxides of Examples 1 to 10 and Comparative Examples 1 to 6 were subjected to an initial activation treatment under the conditions shown in Table 1 to absorb hydrogen, thereby obtaining hydrogen storage materials.
[0050] <Composition analysis: Metal composition analysis> The raw oxide and the hydrogen storage material produced by absorbing hydrogen in the raw oxide were analyzed for the contents of Ba, Zr, In, and Y. The analysis was performed using an X-ray photoelectron spectrometer (Quantum-2000, manufactured by PHI) with Monochromated-Al-Kα radiation (1486.6EV) at 40W as the X-ray source.
[0051] For the pellet samples, the cross section of the sample was analyzed to analyze the average composition in the thickness direction, while for the powder, chip and thin film samples, the sample surfaces were analyzed.
[0052] The metal composition of the raw oxide was determined from the cation composition obtained from the results of XPS analysis of the A and B sites of the perovskite-type oxide (ABO3), and the amount of oxygen required to maintain electrical neutrality was calculated to determine the composition.
[0053] The hydrogen atoms in the hydrogen storage material after hydrogen absorption were analyzed using secondary ion mass spectrometry (SIMS) to measure the hydrogen concentration in the solid (H atom / cm 3 ) was sought.
[0054] The lattice constant of the perovskite crystal was determined by XRD diffraction. From the results of the analysis of six samples from the examples and comparative examples, the average lattice constant was set to 4.20 Å, and the lattice volume (cm 3 / unit cell) was calculated as the amount of hydrogen atoms per unit cell (aom / unit cell).
[0055] In addition, based on the results of the XPS analysis and the composition ratio within the perovskite structure, the number of atoms per unit cell of each element Ba, Zr, In, and oxygen (atom / unit cell) was used, and the composition was described by the atomic % ratio of Ba, Zr, In, O, and H present in one cell.
[0056] Table 1 shows the raw material oxide form, thickness, metal catalyst hydrogen, hydrogen heat treatment conditions, and metal M element for Examples 1 to 10 and Comparative Examples 1 to 6.
[0057] [Table 1]
[0058] Table 2 shows the compositions of the raw material oxides in Examples 1 to 10 and Comparative Examples 1 to 6, and the compositions of the hydrogen storage materials after hydrogen storage.
[0059] [Table 2]
[0060] Table 3 shows the relationship between the hydrogen release temperature and amount of released hydrogen of the activated hydrogen storage materials of Examples 6 to 10 and the raw material oxide.
[0061] [Table 3]
[0062] Details will be described later, but lowering the hydrogen release temperature requires a second perovskite phase that serves as the active site, and this occurs when a portion of the metal M causes structural instability when the Ba content is reduced.
[0063] The amount of the second perovskite phase, which serves as an active site for hydrogen absorption and desorption, can be increased by decreasing the Ba content.
[0064] A comparison of Examples 6, 7, and 8 shows that the amount of hydrogen that can be released increases by decreasing the Ba content.
[0065] On the other hand, not all of the absorbed hydrogen atoms enter or leave the catalyst after activation treatment, and approximately 4.51% to 12.76% of the total can contribute to both absorption and release.
[0066] The remaining hydrogen remains within the phases, remaining in the first perovskite phase and other phases, so long as the operating temperature range is below approximately 800° C. Of these, the first perovskite phase in particular has the function of transporting hydrogen absorbed as protons to the active site and ensuring structural stability.
[0067] The release characteristics in the activation treatment of Examples 6, 7, and 8 shown in Table 3 are that the release is in a state where the initial concentration is unsteady because there is no hydrogen supply to the hydrogen storage material during release and the residual hydrogen concentration in the solid decays. In contrast, in Examples 9 and 10, the hydrogen storage material exhibited a continuous steady-state absorption / desorption phenomenon after activation.
[0068] In addition, since the metal M is different between Examples 9 and 10, it is shown that, regardless of the type of metal M, sufficient hydrogen release and absorption are simultaneously achieved up to about 200°C compared to the state before activation.
[0069] <Hydrogen release behavior and factors> The hydrogen absorption and desorption behavior and factors of hydrogen storage materials and raw oxides were investigated. The details will be explained below.
[0070] <Thermal behavior during hydrogen introduction into hydrogen storage material (raw oxide)> Comparative Example 3 For Comparative Example 4 (raw oxide), the phenomenon in the initial hydrogen absorption and activation process was examined by TG-DTA-MASS.
[0071] In an atmosphere of a mixed gas consisting of 95% nitrogen and 5% hydrogen, the crushed sample pellets were placed on a Pt plate, and the total gas flow rate was 70 Ncc / min. The temperature was raised from room temperature to 800°C at a rate of 10°C / min and observed. The change in d-DTA value in Comparative Example 3 and the change in concentration of m / z=2 (hydrogen) observed with a quadrupole mass spectrometer are shown in FIG. 1, and the results of Comparative Example 4 are shown in FIG.
[0072] Regarding the behavior of d-DTA, first, the result measured under a nitrogen atmosphere was used as a base, and the difference with the measurement value when hydrogen gas was introduced was obtained, and the difference in the DTA value between each measurement point was calculated as d-DTA. H2-N2 was plotted as
[0073] From the behavior of m / z=2 (hydrogen) observed in the quadrupole mass spectrometer in Comparative Example 3 and Comparative Example 4 shown in Figures 1 and 2, it can be seen that in both Comparative Example 3 and Comparative Example 4, the decrease begins in the range of 150°C to 200°C or higher, indicating the presence of a hydrogen consumption reaction. 1 and 2 show only the behavior of the reaction in a hydrogen-mixed atmosphere, excluding the thermal behavior of the raw material oxide itself in a nitrogen atmosphere.
[0074] In addition, the d-DTA value starts to increase from around 150°C as the exothermic reaction progresses, peaking at 185°C and 280°C, respectively, and it can be seen that the overall heat generation amount is greater in Comparative Example 4, which has a lower Ba content.
[0075] No thermal behavior was observed above 400°C. However, hydrogen consumption continued up to 800°C. When the sample was checked after the test, discoloration was observed only on the surface of the pellet that was in contact with the Pt plate. However, no weight loss was observed in the TG measured at the same time.
[0076] <Specific behavior of hydrogen storage materials when reheating> Next, for Comparative Example 3 and Comparative Example 4 after heating in an atmosphere of 5 vol % hydrogen, TG-DTA analysis was carried out in a nitrogen gas atmosphere not containing hydrogen at a heating rate of 10° C. / min.
[0077] As shown in FIG. 3, in both Comparative Examples 3 and 4, endothermic microthermal behavior was observed during the temperature rise process from 150° C. to 200° C., although it was slight.
[0078] 4, in Comparative Examples 3 and 4, the release of hydrogen gas (m / z=2) was observed by mass spectrometry during the above-mentioned temperature increase step. This hydrogen release was due to a low hydrogen concentration and a short treatment time.
[0079] Next, the raw oxides of Examples 4 and 5 were heat-treated in a pure hydrogen atmosphere at 800° C. for 30 hours or more to absorb hydrogen, and the Pt paste was removed to obtain the hydrogen storage materials of Examples 4 and 5. This hydrogen storage material was subjected to TG-d-DTA measurement in a nitrogen atmosphere under the same conditions as described above.
[0080] As a result, as shown in FIG. 5, endothermic behavior was observed in the vicinity of 150° C. to 200° C., which was clearer than the endothermic behavior observed in Comparative Examples 3 and 4.
[0081] Further, a hydrogen release test was carried out for Examples 4 and 5. The hydrogen release behavior of Examples 4 and 5 is shown in FIG.
[0082] From FIG. 6, it was confirmed that in Examples 4 and 5 as well, like Comparative Examples 3 and 4, hydrogen release began in the temperature range of 150 to 200° C.
[0083] <Relationship between Ba content in hydrogen storage materials and thermal behavior and release amount during activation process> Hydrogen was absorbed into the raw oxide of Example 6 under the same conditions as in Examples 4 and 5 to obtain a hydrogen storage material. The relationship between the amount of released hydrogen and the Ba content in Examples 4 and 5, together with the amount of released hydrogen in Example 6, is shown in FIG.
[0084] It is apparent from FIG. 7 that the smaller the Ba content, the greater the amount of released hydrogen. This tendency coincides with the tendency of the amount of heat generated observed at 150° C. to 280° C. in the first hydrogen absorption (initial activation) step.
[0085] <Activation process of raw oxide and control factors of low-temperature hydrogen release and release amount> The hydrogen incorporation reaction into the raw oxide was investigated from the viewpoints of thermal behavior and hydrogen release behavior.
[0086] Generally, the reaction (1) is known regarding the reaction between proton conductors such as barium zirconate and hydrogen. (2) is deoxygenation reduction (endothermic), (3) is water production (exothermic), and (4) is hydration (exothermic).
[0087] H2(g) + 2Ox → 2OH + 2e Qt (1) (total reaction) Ox → 1 / 2O2+ Vo: +2e Q1(2) (deoxygenation) H2(g) + 1 / 2O2(g) → H2O(g) Q2(3) (water production reaction) HO(g) + Ox + Vo: → 2OH Q3(4) (hydration reaction)
[0088] In d-DTA, the thermal response due to the total heat Qt = Q1 + Q2 + Q3 generated during the heating process is observed. Since (2) + (3) + (4) are equivalent to (1), (2) to (4) are each elementary processes for (1).
[0089] In the initial hydrogen absorption (initial activation) process, which is exothermic at 150°C to 280°C, (2) and (3) are considered to be dominant, but (2) is tolerant of proceeding first.
[0090] In other words, in order to promote the deoxidation reaction at low temperatures or under low hydrogen concentration conditions, it is useful to adopt a composition or structure in which the oxygen in the raw material oxide (perovskite oxide) is energetically unstable, or to contact the raw material oxide with a metal catalyst that has deoxidation ability.
[0091] As the temperature of reaction (2) decreases, the behavior of the reverse reaction, the hydrogen release reaction, shifts to a lower temperature, and this is observed as endothermic behavior during release.
[0092] In addition, the amount of hydrogen absorbed and released depends on the reduction in the Ba content. As the amount of unstable oxygen in the structure increases and the Ba composition decreases, the amount of reaction (2) increases, which in turn enhances the amounts of the subsequent reactions (3) and (4), resulting in a difference in the amount of absorbed hydrogen.
[0093] <Identification of the phase and crystal phase that contribute to hydrogen absorption and release: Rietveld analysis> Therefore, we investigated the hydrogen absorption and release and the structure of the perovskite phase by comparing X-ray diffraction images. The X-ray diffractometer (XRD) used was a Rigaku SmartLab 9kW (X-ray: Cu Kα1).
[0094] For Example 5, after the measurement at room temperature, the temperature was raised on the measurement stage while maintaining the N2 atmosphere, and at 200° C., which is the hydrogen release temperature, the XRD profile was obtained again on the same surface as at room temperature.
[0095] FIG. 8 shows the XRD profiles of Comparative Example 4 and Example 5 under N2. 8, both Comparative Example 4 and Example 5 show a perovskite structure, but the peak positions are slightly shifted. In addition, after Example 5 was heated again to 200° C., a part of the perovskite phase disappeared.
[0096] The disappearance of this perovskite phase coincides with the temperature range in which the DTA endothermic peak occurs, indicating that the absorption and release of hydrogen is a thermal behavior that accompanies the disappearance of this layer.
[0097] Although the thermal behavior of Example 5 is affected by thermal expansion due to temperature, the peak position of the remaining phase is a phase that is shifted to the lower angle side compared to Comparative Example 4, and a phase that differs from Comparative Example 4 in both half-width (crystallite diameter) and peak position (lattice constant) remains.
[0098] Therefore, for more detailed structural analysis, the pellets of Comparative Examples 3 and 4 and Examples 4 and 5 were pulverized into powder, XRD diffraction patterns were obtained, and Rietveld analysis was performed under the following conditions to identify in detail the effective phase for hydrogen release and desorption. Table 4 shows a comparison of the perobst constituent phases identified by Rietveld analysis in Comparative Examples 4 and 5 and Examples 4 and 5.
[0099] (Rietveld analysis conditions) Database used: ICDD, Software used: PDXL2 (Rigaku) Analysis software: RIETAN-FP (profile: extended pseudo-Voigt function) Database:ICSD
[0100] [Table 4] As shown in Table 4, it has a perovskite first phase and a perovskite second phase, and the content of the perovskite first phase is at least 60 mol % or more.
[0101] As shown in Table 4, in Examples 4 and 5 in which hydrogen was absorbed by activation treatment, the molar abundance ratio of the perovskite second phase was increased and the lattice constant was also slightly expanded compared to Comparative Examples 4 and 5, respectively.
[0102] In addition, in comparing Example 4 and Example 5, a positive correlation is observed between the amount of the perovskite second phase produced in the activation treatment step and the amount of hydrogen released shown in FIG.
[0103] Therefore, it is understood that by reducing the amount of Ba added to the raw material oxide, a larger amount of the second perovskite phase can be obtained after hydrogen introduction.
[0104] Furthermore, the expansion of the lattice constant is a reaction in which two hydrogen atoms newly enter the raw material oxide structure through the above reaction formulas (1) to (4), and therefore it can be said that the expansion is due to the introduction of hydrogen.
[0105] Considering that one perovskite phase disappears during the re-heating process after hydrogen absorption mentioned above, the second perovskite phase analyzed is the phase that is directly involved in the absorption and release of hydrogen at low temperatures.
[0106] <Definition of the content of the second perovskite phase that contributes to low-temperature absorption and release> That is, the second perovskite phase is directly involved in hydrogen release at low temperatures, and has a crystal lattice constant that is 0.02 Å or more larger than the crystal lattice constant of the first perovskite phase. From Example 4, it is clear that the inclusion of 5 mol % or more of this perovskite second phase increases the absorption and release of hydrogen.
[0107] <Identification of the phase and crystal phase that contribute to hydrogen absorption and desorption: Balance of hydrogen atoms in solids> For the hydrogen storage materials of Comparative Examples 3 and 4 and Examples 4 and 5, the hydrogen concentrations in the hydrogen storage materials were determined by secondary ion mass spectrometry (SIMS).
[0108] In the case of a Pd catalyst (50 nm) using a metal catalyst, the analysis was performed while the lower surface, which had been removed by surface etching with Ar ions, was further etched with Ar ions. In addition, when the metal catalyst was a Pt paste layer, the analysis was performed after polishing with sandpaper. For samples without a metal catalyst, the above treatment was not performed.
[0109] SIMS measurement profiles in Comparative Example 3 and Example 4, and Comparative Example 4 and Example 5 are shown in Fig. 9. It can be seen from Fig. 9 that the hydrogen concentration in the hydrogen storage material increases by about one order of magnitude after the activation treatment in a hydrogen atmosphere.
[0110] The ion current of m / z=2 detected in the hydrogen release test in FIG. 6 described above was quantified using the quantification coefficients described above based on the ECOS method, and the molecular weight of hydrogen released in the range of room temperature to 800°C was integrated. Hydrogen molecule conversion coefficient for ion current at m / z=2 based on the ECOS method: 3.96×10 22 (N m / C) N m : number of molecules, C: Coulomb
[0111] In addition, the true density of the hydrogen storage material was calculated using the weight of the sample used for evaluation, the composition formula obtained from the results of elemental analysis, and 4.20 Å as the lattice constant obtained from the results of the XRD analysis described above.
[0112] The volume of the hydrogen storage material was calculated from the obtained true density and the weight of the sample used in the hydrogen release test. The hydrogen atomic weight was calculated as twice the total molecular weight of released hydrogen, and the average concentration of released hydrogen atoms within the solid hydrogen storage material before hydrogen release was calculated.
[0113] For the hydrogen concentrations before hydrogen release in Examples 4 and 5, the total hydrogen atom concentration in the entire solid of the hydrogen storage material, the release contribution concentration, and the ratio thereof are shown in Table 5, using the above two methods.
[0114] [Table 5]
[0115] As shown in Table 5, the hydrogen concentration in the hydrogen storage material measured by SIMS is higher than the amount of released hydrogen present in the hydrogen storage material. During the temperature rise process from room temperature to 800°C, the proportion of hydrogen atoms released as hydrogen gas outside the hydrogen storage material was several percent to 10% of the total.
[0116] It can be seen that in Example 4, which has a higher Ba content and a smaller molar ratio of the second perovskite phase, the proportion of hydrogen that can be exchanged between the inside and outside of the hydrogen storage material is small, while in Example 5, which has a lower Ba content and a larger molar ratio of the second perovskite phase, the proportion of released hydrogen is higher.
[0117] In this way, the molar ratio of the second phase and the ratio of hydrogen atoms that can exchange with the outside among all hydrogen atoms in the hydrogen storage material are in agreement, making it clear that the second phase contributes to the absorption and release of hydrogen.
[0118] On the other hand, hydrogen also remains in the first perovskite phase that remains after hydrogen release at low temperatures. Since a higher temperature environment is required to release hydrogen from the first perovskite phase that remains on the low-temperature release side, it is self-evident that more stable (enthalpicy unfavorable for release) hydrogen atoms remain.
[0119] <Characteristics and Functions of Perovskite Phase 1> The first perovskite phase that remains after low-temperature release also contains unreleased hydrogen atoms, and these remain even at higher temperatures. The function of these hydrogen atoms was identified through the following investigation.
[0120] The introduction of hydrogen into the first perovskite phase may follow the formula (1) or may take the following forms (1) and (5) to (8) by reaction with oxygen vacancies and residual electrons formed in advance in the raw oxide by impurity doping according to the formula (2) described above and the formula (9) described below, or with holes according to the formula (11) described below.
[0121] H2(g) + 2Ox → 2OH· + 2e (electron production) (1) H2(g) + O o x + Vo: → {H - -Vo:} + + OH· (5) H2(g) + 2Vo: + 2e → 2{H - -Vo:} + (electronic consumption) (6) H2(g) + 2O o x + 2h → 2OH (hole consumption) (7) e + h → null (recombination) (8)
[0122] The above-mentioned (5) is the overall reaction when (6) + (7) proceed in equal amounts. Which reaction predominates depends on the amount of electrons and holes present in the hydrogen storage material. The initial amount of holes is controlled by the composition of the raw material oxide, as shown in Figure 10.
[0123] On the other hand, the present inventors have found the existence of an electron consuming reaction in the activation step based on the following experimental investigation.
[0124] A raw oxide in which M was In on a Pd film was formed on a Pd foil (50 μm), which is one of the metal catalysts, by magnetron sputtering using the method described in the examples, thereby obtaining a raw oxide with a metal catalyst of Example 9.
[0125] The obtained thin film of the raw material oxide has a thickness of about 1 μm. As can be seen from the SIMS analysis profile in Figure 9, this thickness of 1 μm is a thickness that allows hydrogen atoms to be absorbed throughout the entire thickness of the raw material oxide by performing hydrogen activation treatment.
[0126] As shown in Figure 11, a laminate (hydrogen storage material) consisting of a thin film (1 μm) of raw oxide / Pd foil (50 μm) was laminated with a high-temperature gasket (Thermiculite) on each side to form an isolated two-chamber cell. A pressure of 50 kPa_g was applied to the hydrogen introduction chamber using He gas to confirm that no gas was passing through to the raw oxide side.
[0127] As shown in FIG. 11, Pt meshes were attached as electrodes on both sides, and these were led out to the outside of the cell through welded Pt wires to measure the voltage outside the cell. Nitrogen gas was passed through the surface of the raw oxide, and a nitrogen-based gas containing 50% H2 was passed through the Pd foil side. The raw oxide surface was connected to the positive terminal, and the Pd foil was connected to the negative terminal.
[0128] In addition, a quadrupole mass spectrometer was installed at the outlet of the nitrogen gas flowing into the raw oxide side to measure H2 gas, N2 gas, and O 2、 The cell temperature was increased from room temperature to 550°C at a rate of 10°C / min while simultaneously observing the H2O production behavior and the potential difference between both ends. The raw oxide does not come into direct contact with hydrogen gas.
[0129] However, because the Pd foil, a metal catalyst, is a hydrogen permeable membrane, the raw oxide comes into contact with atomic hydrogen at the interface through the Pd, and receives a supply of hydrogen. In addition, because Pd has the catalytic ability mentioned above, it is believed that the raw oxide will be activated even if it does not come into direct contact with hydrogen gas. Using this device, the electrical behavior of the raw oxide and the characteristics of the released gas during the activation process were examined.
[0130] FIG. 12 shows the profile during the activation treatment of the raw oxide with the metal catalyst in Example 9. The O2 generation peak at 167°C to 200°C indicates the occurrence of the aforementioned deoxidation, and immediately afterwards the voltage drops temporarily. After hydrogen is introduced, the voltage rises temporarily because the potential difference between the two sides of the hydrogen storage material is different, but the aforementioned deoxidation reaction produces electrons, and the raw oxide phase becomes electronically conductive, causing a short circuit between the two terminals and a drop in voltage. The voltage then drops from 300°C to 550°C, indicating an improvement in the short circuit condition and corresponding to the consumption of electrons within the hydrogen storage material.
[0131] After that, the hydrogen concentration in N2 increases between 350°C and 400°C. This indicates that hydrogen is absorbed at the interface of the raw oxide thin film on the Pd foil side, and at the same time, hydrogen is released from the surface in contact with nitrogen gas.
[0132] As the voltage increases from 350°C to 550°C, the production of HO, which had decreased once, also increases. This suggests that the deoxygenation (2), water production (3), and electron consumption reactions (4) shown in the above reaction formula continue even after 550°C.
[0133] In addition, the resistance between both terminals at room temperature was measured using the DC 4-terminal method, and the initial resistance was 1.77×10 -11 (S / cm), after testing 8.82×10 -4 (S / cm), and the electrical conductivity was improved.
[0134] Proton transport within a solid is slow when the hydrogen bonding is strong, because the proton of a hydroxyl group forms a hydrogen bond with a nearby lattice oxygen atom to form a new hydroxyl group and then moves. According to the above reaction formula (5), the polarizability around the lattice oxygen changes, which changes the hydrogen bonding property and can improve the transportability of protons. If the transportability is high, the diffusion coefficient of the material transport from the inside of the hydrogen storage material to the release surface is high, and as a result, more hydrogen atoms can be stored and released within the solid. Therefore, the first perovskite phase plays a role in promoting the transportability of OH· within the solid to the second perovskite phase, which is the hydrogen release point. It plays a role in increasing the amount of hydrogen stored and released in the hydrogen storage material.
[0135] Regarding the thermal behavior of the activation process described above, no thermal behavior was observed above 400°C, while hydrogen consumption continued up to 800°C. This makes it possible to produce a thermally stable phase that is formed at a relatively slow rate in the high temperature range of 400°C to 800°C.
[0136] <Definition of the content of the first perovskite phase> The first perovskite phase ensures the above-mentioned functions, and is preferably at least 60 mol% of the total content. By having the first perovskite phase content of 60 mol% or more, the basic structure and the transport of OH· are maintained, contributing to the repeated absorption and release of hydrogen.
[0137] The content of the first perovskite phase is preferably 90 mol % or less. In the hydrogen storage material of the present invention, the second perovskite phase is considered to contribute greatly to hydrogen absorption and desorption, and if the content of the first perovskite phase exceeds 90 mol %, the second perovskite phase, which is directly involved in hydrogen desorption at low temperatures, decreases.
[0138] <Explanation of the method for promoting deoxidation by destabilizing oxygen in the raw oxide> The mechanism by which oxygen becomes destabilized by reducing the amount of Ba arises from the arrangement of cations in the perovskite structure.
[0139] The cation radius of each of the cations constituting the perovskite oxide used in the present invention is as follows.
[0140] (cation radius) Ba: 1.35 Å In:0.81 Å Y: 0.93 Å Zr: 0.80 Å
[0141] By decreasing the Ba content below 1.0, the lattice constant decreases, because the Ba sites are occupied by smaller In or Y, which generates a contraction strain.
[0142] The above-mentioned contraction strain is so great that it affects the more macroscopic average lattice constant of the entire hydrogen storage material observed by XRD. In the vicinity of the unit lattice in which In and Y occupy the A sites of Ba, there is a large strain locally, which reduces the stability of the nearby oxygen atoms.
[0143] From the viewpoint of lowering the hydrogen release temperature, reducing the amount of Ba is an effective means in terms of material and structural design, and increasing the Ba reduction is a means of increasing the amount of release.
[0144] It was confirmed as follows that the metal M occupies a part of the Ba site in the hydrogen storage material according to the embodiment of the present invention.
[0145] In systems using yttrium (Y) as a trivalent cation on the B site, it is known that in compositions where the Ba occupancy rate is less than 1, the missing Ba sites are occupy by yttrium (Y).
[0146] Using this method, in the case of indium (In), confirmation was carried out by comparing the tendency between the amount of water vapor adsorbed to the raw oxide and the amount of Ba according to reaction formula (3).
[0147] The oxygen vacancies described in reaction formula (2) are vacancies that are generated when lattice oxygen is deoxidized in a reducing atmosphere. The amount of oxygen vacancies generated by doping with low-valent cation impurities increases or decreases depending on the amount of doping element added. Y2O3+ 2Zr zr + Oo x → 2Y zr + Vo:+2ZrO2(9) HO(g) + Oo x + Vo: → 2OHo· (10) 2Ba Ba x + Vo:+ Y2O3→2Y Ba + Oo x +2BaO(11)
[0148] When there is a Ba deficiency, a structure is formed in which trivalent cations occupy the Ba sites according to reaction formula (11), so the amount of oxygen vacancies decreases and the amount of hydration in reaction formula (3) decreases.
[0149] Comparative Example 3 and Comparative Example 4 are perovskite oxides in which Y of the metal (M) is replaced with In. In order to verify the structural effect of reducing the amount of Ba, the oxides were dried by increasing the temperature from room temperature to 850°C at a rate of 10°C / min in a dry N2 atmosphere using TG-DTA, and then held at 850°C, mixed with water vapor equivalent to 23°C and 100% Rh, and after a holding time of 20 minutes, cooled to 50°C in 100°C increments, and the amount of hydration of Comparative Example 3 and Comparative Example 4 was measured from the weight increase at that time. The measurement results are shown in Table 6.
[0150] [Table 6]
[0151] From Table 6, Comparative Example 4, which has a composition with a smaller Ba content than Comparative Example 3, has a low hydration amount of about 1 / 10. In other words, this means that the amount of impurity-type oxygen vacancies is about 1 / 10. As can be understood from the above reaction formula (11) in which Y is replaced with In, it can be seen that trivalent In occupies the A site position, thereby greatly reducing the oxygen vacancies.
[0152] On the other hand, as shown in FIG. 13, the result of Rietveld analysis confirmed that the A site had a structure containing both Ba and In.
[0153] <Catalytic effects and catalyst materials in the activation process of raw oxides> The activation of the raw material oxide can be promoted by catalytic action in the reactions of formulas (2) and (3), which are the elementary steps of reaction formula (1) above. In general, catalysts that promote deoxygenation and the water production reaction by contact with hydrogen and oxygen, such as hydrogen dissociation, oxidation, and oxygen reduction, can be suitably selected.
[0154] In general, metals known to have high deoxidizing ability include Pd, Ni, Co, and Mo. In addition, precious metals such as Pt, Pt, Pd, and metallic Ni are useful for hydrogen dissociation and oxidation reactions, and precious metals such as Pt and Pd, and metals such as Ni, Co, and Mn can be used for oxygen adsorption and reduction.
[0155] Oxides are also effective as long as they can maintain a functional oxidation state at high temperatures and in a low-oxygen environment. Among these metals, Pt, Pd, Ni, and Co catalysts are the easiest to use because they are multifunctional materials that possess all the functions required to promote reactions in one material. The steps of the above reaction formulas (2) and (3) can also be accelerated by using mixtures or alloys of monofunctional and bifunctional catalysts, each of which performs one or two functions.
[0156] <Embodiment of catalytic metal in raw material oxide activation> Such a catalyst may be placed in a state where it is brought into contact with the raw material oxide so as to ensure solid-solid contact with the raw material oxide in the activation step.
[0157] In one embodiment, the catalyst may be in contact with an apparatus used in the activation step, such as the function of a Pt plate in TG-DTA-MASS analysis. In another embodiment, the catalyst may be in solid-solid contact with the raw oxide by coating, electroless plating, deposition, impregnation, or support of a metal paste.
[0158] It is also possible to mix it into the raw oxide as an impurity oxide phase, or to separate and precipitate a metal phase during the process as in the above-mentioned example of In, and have it function as a catalyst within the process.
[0159] As yet another embodiment, it is also possible to use a hydrogen-permeable metal having the catalytic action described above, as will be described later.
[0160] By depositing and forming a raw oxide on the hydrogen-permeable metal foil with catalytic activity using the sputtering method, PLD method, atmospheric plasma method, sol-gel method, or paste, the raw oxide can be given the ability to absorb and release hydrogen.
[0161] <Use of materials activated by catalytic metals> The perovskite-type hydrogen storage material of the present invention obtained by activating the raw oxide by the above-mentioned method can be used as a perovskite-type oxide material support by subjecting the catalyst to peeling and dissolving treatment as necessary.
[0162] Furthermore, when the final use is as a catalyst support, the metal catalyst can be selected taking into consideration its function as a catalytic active material for another target reaction. This makes it possible to peel off and remove the catalyst used in the activation step in which hydrogen is absorbed in the raw oxide, and obtain the perovskite oxide hydrogen storage material of the present invention carrying the desired metal active material, without the need to support a new catalytic active material for the target reaction.
[0163] Furthermore, when a raw oxide is deposited or formed on a hydrogen-permeable metal foil by a sputtering method, a PLD method, an atmospheric plasma method, a sol-gel method, a paste drying method, or the like, and an activation treatment is performed, the resultant may be used as it is depending on the purpose, or a part or all of the hydrogen-permeable metal foil may be dissolved and removed with an acid before use.
[0164] Industrially, the material can be used as an anode material for batteries that use hydrogen or metal hydrides, such as fuel cells, and as a sheet material that promotes reactions such as steam reforming.
[0165] <Appearance of electronic conductivity during the activation process of raw oxide> By excessively reducing the amount of Ba, it is possible to generate an impurity phase other than the perovskite phase due to phase equilibrium. As described later, it is also possible to intentionally impart functions to the impurity phase.
[0166] By selecting elements with a small oxide band gap, it is possible to obtain a hydrogen storage material with better electronic conductivity. In addition, by using an excess of barium in the A site, it is possible to intentionally give an oxide phase different from the perovskite consisting of M2O3.
[0167] It is known that when the metal (M) is Y, Y2O3 is generated by reducing the amount of Ba. As shown in the XRD spectrum diagram in Figure 14, it was confirmed that when the metal (M) is In, a large amount of In2O3 is generated by reducing the amount of Ba.
[0168] Such impurity phases are reduced from oxides to metallic In during the activation step, as shown by the Rietveld analysis of Comparative Example 4 and Example 5 for the non-perovskite phases.
[0169] By intentionally forming a phase that is not included in the perovskite structure, it is also possible to use it as a means for imparting electronic conductivity to the hydrogen storage material. The content of impurity phases having non-perovskite structure is analyzed in Table 7.
[0170] [Table 7]
[0171] Such a phase consists of In or an oxide of In when the metal (M) is In, and S The oxide-metal state can be detected by the spectrum. Measured from the XPS In3d5 / 2 spectrum If the bond energy is 443.851 eV or less, it can be determined that the In is metallic, rather than an oxide, based on the relationship in Figure 15. In order to ensure electrical conductivity by providing such a phase, it is preferable to contain 2.0 to 11 mol of the third phase. By containing this phase at 5 mol% or more, electrical conductivity is increased, and the transfer of electrons involved in the absorption and release of hydrogen is promoted.
[0172] The hydrogen storage material can be confirmed to function if its electrical conductivity is higher than that of the raw oxide. In particular, the electrical conductivity measured by the DC four-terminal method at room temperature is 4.0×10 -4 In practical terms, it is preferable that the electrical conductivity be 1.0 S / cm or more. Table 9 shows the electrical conductivity before and after hydrogen absorption in Examples 9 and 10.
[0173] [Table 8]
[0174] <Explanation of metal catalyst effect> A comparison was made between cases with and without a metal catalyst. FIG. 16 shows the relationship between the maximum treatment temperature during hydrogen absorption and the hydrogen atom concentration in the hydrogen storage material shown in Table 6.
[0175] It can be seen from FIG. 16 that by contacting with a metal catalyst, it is possible to cause a larger amount of hydrogen atoms to be absorbed in the perovskite oxide, regardless of the type of metal M.
[0176] Further, for the hydrogen storage material of Example 9 and the hydrogen storage material of Comparative Example 6, the release of hydrogen from the hydrogen permeable membrane was attempted. In Example 9, in the experimental apparatus of FIG. 11, the Pd foil surface was brought into contact with 50% hydrogen gas, and the raw oxide was placed facing the nitrogen gas surface. In Comparative Example 6, the gas flow was reversed, and the raw oxide was brought into contact with 50% hydrogen gas, with the Pd foil surface placed on the nitrogen gas surface, as shown in FIG. In Comparative Example 6, the temperature was raised to 600° C., but no hydrogen permeation was observed. Therefore, only in Comparative Example 6, the hydrogen concentration in contact with the raw oxide was increased to 100%, and hydrogen permeation was confirmed. The results are shown in FIG.
[0177] The results in Figure 18 also show that, rather than contacting the raw oxide with a high concentration of hydrogen gas, contacting hydrogen gas with a metal catalyst via the metal catalyst or supplying hydrogen gas to the interface between the metal oxide and the raw oxide results in the action of the metal catalyst, thereby promoting the introduction of hydrogen atoms into the raw oxide.
[0178] From these results, it will be easily understood that similar effects can be obtained in the case of a raw oxide having a metal catalyst supported thereon, as shown in Figure 19, and that this can be used as one embodiment of the present invention.
[0179] Furthermore, even if the thickness of the raw oxide is 1 μm, taking into consideration that the particle size of a typical catalyst support is submicron to several microns, it can be easily understood by a person skilled in the art that even in the form of use as a particulate catalyst support as shown in Figure 19, hydrogen release and absorption can be performed continuously, especially in the presence of a metal catalyst. [Industrial Applicability]
[0180] The hydrogen storage material of the present invention can be used as a catalyst or catalyst support for temporary storage and release of hydrogen in hydrogen storage applications, steam reforming, fuel cell anode catalysts, dehydrogenation reactions, nitrogen oxide purification reactions in exhaust gases, and the like.
Claims
1. The basic structure is ABO 3 a hydrogen storage material having a perovskite oxide structure represented by the formula: wherein the A site is barium (Ba), the B site is zirconium (Zr), and a part of the A site and / or the B site is substituted with a metal (M), and wherein hydrogen (H) is contained within the perovskite oxide structure; The elemental composition is Barium (Ba) is 12 to 21 atomic percent, Zirconium (Zr) is 8 to 21 atomic %; Oxygen (O) is 50 to 62 atomic percent, Metal (M) is 4 to 16 atomic %; Hydrogen (H) is in the range of 2 to 13% atomic percent; A hydrogen storage material having a perovskite first phase and a perovskite second phase obtained by Rietveld analysis of an X-ray diffraction spectrum, the content of the perovskite first phase being at least 60 mol % or more. Here, M represents indium (In) or yttrium (Y).
2. The metal (M) is 3 2. The hydrogen storage material according to claim 1, wherein the hydrogen is arranged at both the A site and the B site of the structure.
3. The hydrogen storage material as described in claim 2, characterized in that the content of the perovskite first phase is 90 mol % or less.
4. The crystal lattice constant of the perovskite second phase is 0.02 Å or more larger than the crystal lattice constant of the perovskite first phase; 4. The hydrogen storage material according to claim 3, further comprising at least 5 mol % of the perovskite second phase.
5. The hydrogen storage material according to claim 3, characterized in that the electrical conductivity is 4.0×10 −4 S / cm or more.
6. Further comprising 2.0-11 mol% of a third phase consisting of In or an oxide of In; 6. The hydrogen storage material according to claim 3, wherein the binding energy of the third phase measured from an In3d5 / 2 spectrum of XPS is 443.851 eV or less.
7. Further having a metal catalyst on the surface, The hydrogen storage material according to any one of claims 1 to 6, characterized in that the metal catalyst is at least one selected from the group consisting of palladium (Pd), platinum (Pt), nickel (Ni), and cobalt (Co).
8. The shape is particulate, 8. The hydrogen storage material according to claim 7, characterized in that the metal catalyst is supported on the surface of the material.
Citation Information
Patent Citations
Perovskite type composite oxide
JP2008100902A
Method of improving proton conductivity of the Proton Ceramic Fuel Cell electrolyte
KR1020170099195A
Perovskite oxide containing hydride ion, and method for manufacturing same
WO2013008705A1
Proton conductor
WO2015114684A1
Proton conductor and electrochemical device using same
WO2019235025A1
